International Express Upper-Intermediate. Students Book - Wallwork, Adrian (Oxford Oxford University Press, 2001)
Intenational Express is a multi-level general English course for adult professioal learners. It has been designed to meet the practical language requirements of adults who need to communicate confidently in English at work, for trawel, and in variety of social situations.
Keywords: English Practice